Lytic bacteriophages induce the secretion of antiviral and proinflammatory cytokines from human respiratory epithelial cells - Zamora, Paula F.; Reidy, Thomas G.; Armbruster, Catherine R.; Sun, Ming; Van Tyne, Daria; Turner, Paul E.; Koff, Jonathan L.; Bomberger, Jennifer M. (PLOS Biology, 2024)
Phage therapy is being explored to treat multidrug-resistant bacterial infections, but the possible direct effects of phages on the human host are less well understood. This study shows that therapeutic phages can be detected by epithelial cells of the human respiratory tract, eliciting proinflammatory responses that depend on specific phage properties and the airway microenvironment.